Symbiotic symmetries of the two-Higgs-doublet model - Ma, Ernest; Maniatis, Markos (Physics letters, 2010)
The new phenomenon of symbiotic symmetries is described in the context of the Two-Higgs-Doublet Model (THDM). The quartic potential has two or more separate sectors with unequal symmetries, but these unequal symmetries persist even though the different sectors are renormalized by one another. We discuss all such symmetries of the THDM, consistent with the SU(2)×U(1) gauge interactions, using the Pauli formalism.